2x + 7b is an expression. Since it is not an equation it cannot be solved. Furthermore, as an expression, there is no meaninful simplification, either.
The given expression can be simplified to: 3b-a
a + 7b + 2c
It is: 19b+7b = 26b
It is: 7b+10 simplified
If you mean: -3*(-2b-3)+7b then it is an algebraic expression that can be simplified to 6b+9+7b = 13b+9
9a + 7b *remember to look and understand the letters!*
100a2 - 49b2 is the difference of two perfect squares. Therefore, it is equal to the sum times the difference of the roots: (10a + 7b)(10a - 7b)
4b plus 7b plus 5 will equal 11b plus 5. When you have two variables that are the same you can add the two numbers with the variables remaining the same.
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
4b - 3
The GCF is 7b.
6a + (7b - 4a - 8b) = (6a - 4a) + (7b - 8b) = 2a - b
If you mean: 6(-3b-1)+2(7b-1) then it is -4b-8 simplified
add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
(8b + 7)(7b + 9)
7b + 16 = 5b + 247b - 5b = 24 - 162b = 8b = 4
3a + 4b - 5 - 1a + 7b + 3 - 1b 2a + 10b - 5 + 3 2a + 10b - 2
If: 6b+21 = 7b-21 Then: 6b-7b = -21-21 And: -b = -42 So: b = 42